1990
DOI: 10.1073/pnas.87.4.1362
|View full text |Cite
|
Sign up to set email alerts
|

Observations of reaction intermediates and the mechanism of aldose-ketose interconversion by D-xylose isomerase.

Abstract: Crystallographic studies of D-xylose isomerase (D-xylose ketol-isomerase, EC 5.3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
1
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 21 publications
4
64
1
2
Order By: Relevance
“…Studies using deuterated solvents have shown that enzymes and bases perform the aldose/ketose transformation through a mechanism involving a cis 1,2-enediol intermediate, whereby the bonding electron pair at C-2 moves through the carbon skeleton to C-1 (Scheme 2A) (17,18). Kinetic studies of isomerization reactions report that certain acids and metals are able to transfer the hydrogen directly through a hydride shift between C-2 and C-1 (Scheme 2B) (19). Corma et al showed that Sn incorporated in the framework of zeolite Beta is a good catalyst for the MPV reaction between alcohols and ketones that requires adequate Lewis acidity in the catalyst to polarize the carbonyl group in the ketone while also coordinating both the alcohol and the ketone to facilitate a hydride shift between them (12,13).…”
Section: Resultsmentioning
confidence: 99%
“…Studies using deuterated solvents have shown that enzymes and bases perform the aldose/ketose transformation through a mechanism involving a cis 1,2-enediol intermediate, whereby the bonding electron pair at C-2 moves through the carbon skeleton to C-1 (Scheme 2A) (17,18). Kinetic studies of isomerization reactions report that certain acids and metals are able to transfer the hydrogen directly through a hydride shift between C-2 and C-1 (Scheme 2B) (19). Corma et al showed that Sn incorporated in the framework of zeolite Beta is a good catalyst for the MPV reaction between alcohols and ketones that requires adequate Lewis acidity in the catalyst to polarize the carbonyl group in the ketone while also coordinating both the alcohol and the ketone to facilitate a hydride shift between them (12,13).…”
Section: Resultsmentioning
confidence: 99%
“…8 -barrel fold they have different catalytic mechanisms. d-Xylose isomerase exploits the hydride shift mechanism Collyer & Blow, 1990!. TIM follows the enolization mechanism Rose, 1975!, which has also been accepted for several other isomerases including both metal-dependent~mannose-6P, l-arabinose, and l-fucose isomerases!…”
mentioning
confidence: 99%
“…2). However, the amino acids involved in substrate binding and isomerization (5,8,9) and the spacing between them are well conserved. These residues are not situated in one domain, but they are spread out along the primary structure.…”
Section: This Fragment Was Sequenced In Both Directions Showingmentioning
confidence: 99%
“…The net traffic (calculated from [2], S. violaceoniger [3], A. missouriensis [4], Ampullariella species [5], Clostridium thermosulfurogenes [6], Clostridium thermohydrosulfuricum [7], B. subtilis [8], and E. coli [9]. Numbers are for the T. thermophilus enzyme.…”
Section: This Fragment Was Sequenced In Both Directions Showingmentioning
confidence: 99%
See 1 more Smart Citation